2015
DOI: 10.1007/s00228-015-1899-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower CYP2C9 activity in Turkish patients with Behçet’s disease compared to healthy subjects: a down-regulation due to inflammation?

Abstract: Contrary to expectation, the CYP2C9 activity was lower in Turkish BD patients compared to healthy subjects. As this seems not to be due to colchicine treatment, our hypothesis is that inflammation related to BD might have caused the down-regulation of the CYP2C9 activity due to immune cytokine reactions. The ultra-rapid metabolism of CYP2C9 substrate drugs in the Swedish patient was not due to her BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 86 publications
1
20
1
Order By: Relevance
“…Phenoconversion is also observed during inflammatory comorbidities . For example, patients with Behçet's disease have been shown to have lower CYP2C9 activity …”
Section: Discussionmentioning
confidence: 99%
“…Phenoconversion is also observed during inflammatory comorbidities . For example, patients with Behçet's disease have been shown to have lower CYP2C9 activity …”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients with BD had about 2.5‐fold increased lansoprazole metabolic ratio compared to the controls suggesting that CYP2C19 activity is markedly reduced in these patients. Consistent with this finding, in our previous study , we reported a significantly decreased CYP2C9 activity in the same patients with BD. Immune cytokine reactions in BD might have caused the down‐regulation of CYP2C9 as well as of the CYP2C19 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In another in vivo study, colchicine did not significantly change CYP2C19 activity in rat . We also recently showed that colchicine does not have any significant effect on losartan metabolism, which is a probe reaction for phenotyping of the CYP2C9 in vivo in human beings . In this study, we demonstrated that colchicine did not exert any change in the CYP2C19 activity of six patients who used the drug for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations